Identifying germination opportunities for threatened plant species in episodic ecosystems by linking germination profiles with historic rainfall events - Elliott, C.P.; Lewandrowski, W.; Miller, B.P.; Barrett, M.; Turner, Shane (2019)
Dynamic processes of seed germination, influenced by niche-climate interactions, underpin successful seedling establishment. For threatened species with niches restricted to specific landforms, such as Banded Ironstone Formations (BIF), understanding germination opportunities in relation to long-term rainfall patterns can be critical for management. We quantified germination profiles (germinating fraction and speed with varying dormancy states) from six taxonomically diverse threatened species that are endemic to BIF in Western Australia, and related this to historic rainfall patterns and events. The upper limit of the germination profiles (i.e. for dormancy-alleviated seed) was 1.2-60 times higher (germinating fraction Gmax) and 1.1-4 times faster (T10) than the lower profile limit (i.e. dormancy not alleviated) in the physiologically dormant species studied (Tetratheca paynterae Alford subsp. paynterae and T. erubescens J.P.Bull Ricinocarpos brevis R.J.F.Hend. & Mollemans Darwinia masonii C.A.Gardner Lepidosperma gibsonii R.L.Barrett). Seeds of Banksia arborea (C.A.Gardner) A.R.Mast & K.R.Thiele are non-dormant and had a germination profile similar to this upper limit. The minimum period of moisture required for germination was less than eight consecutive days and our simple moisture model, based on historic rainfall patterns for their localities, indicated that these periods have likely occurred 16 times in the last 100 years. We suggest that these BIF species are likely committing to germination during heightened rainfall periods, despite these periods being infrequent and irregular. Understanding the germination profiles of range-restricted species provides important insights into the environmental filters regulating recruitment and supports the development of more effective management and conservation approaches for protecting these species.